Retinal vein changes after treatment with aflibercept and PRP in high-risk proliferative diabetic retinopathy - Zhao, Hui; Wang, Jundong; Li, Shuting; Bao, Ying; Zheng, Xiaoxia; Tao, Yuan; Wang, Hong (Frontiers in Medicine, 2023)
Objective: The objective of the study was to investigate the effectiveness of aflibercept and panretinal photocoagulation（PRP） in the treatment of proliferative diabetic retinopathy (PDR). Methods: A retrospective analysis was performed on 59 patients (59 eyes) with high-risk PDR who were treated with aflibercept and PRP between January 2018 and December 2019. The best corrected visual acuity (BCVA), central foveal thickness (CFT), and retinal vein diameter post-treatment were compared to those before the treatment. Results: The best corrected visual acuity (BCVA) at 6 months (0.49 ± 0.14 logMAR), 12 months (0.54 ± 0.15 logMAR), 18 months (0.48 ± 0.15 logMAR), and 24 months (0.51 ± 0.15 logMAR) post-treatment were superior to the pre-treatment measurement (0.65 ± 0.18 logMAR). The central foveal thickness (CFT) at 6 months (310.67 ± 52.53 µm), 12 months (295.98 ± 45.65 µm), 18 months (282.56 ± 43.57 µm), and 24 months (281.53 ± 51.16 µm) post-treatment were lower than the pre-treatment measurement (456.53 ± 51.49 µm); the retinal vein diameter at 12 months (310.13 ± 24.60 µm), 18 months (309.50 ± 31.58 µm), and 24 months (317.00 ± 27.54 µm) post-treatment were lower than the pre-treatment measurement (361.81 ± 30.26 µm). Conclusion: Aflibercept intravitreal injection and panretinal photocoagulation may morphologically reverse retinal vein diameter and venous beading in high-risk proliferative diabetic retinopathy.